Development of sequential combination of anaerobic-aerobic and ozonation process for treating effluents from distillery of ethanol fermented from molasses - Evangelista-Ordoño, Emma (2013)
Distilleries are amongst the most highly polluting industries with reference to the extent of water pollution both in terms of quantity of the wastewater generated as well as the extent of pollution load in the effluent stream. This study aimed to compare the three reactor (AD I + II) at 3 days hydraulic retention time (HRT) each phase; sequencing batch aerobic biological processes (AER) at 3 days HRT and ozonation (OZ) as a 30 minute pretreatment, 30 minute intermediate process and 4 hour post-treatment. In scheme A (ADI + II, AER, OZpost) and scheme B (AD I + II, OZint, AER, OZpost), 41.1 ± 14.4% COD is removed in AD I + II, phase 1 and 2 of which were run at 1.75±0.15 and 1.02±0.25 gCOD/L/d organic loading rates. Biogas production was 0.98±0.53 L/g COD removed in the anaerobic digesters (AD I + II). Color was not removed in the biological processes. The intermediate 30 minute ozonation and AER (scheme B) affected 35.1±4.4% COD removal for the effluent after AD I + II treatment while 19.4±13.0% COD removal when only AER was applied (scheme A). In scheme C, ozonation pretreatment achieved a significant reduction in COD and color levels. The percent COD reduction based on the influent of the first step were 15% in the ozonation pre-treatment, 32.9% in AD I and II, 10.2% in the aerobic treatment and 26.4% in ozonation post-treatment. In the post ozonation, both pseudo-first order and pseudo-second order rate equations expressed in terms of the concentration of organic matter (COD) and color level (PCU) were curve-fitted. Calculations showed that assuming constant ozone concentration in the wastewater during ozonation, the COD and color reductions are best described by pseudo-first order rate equation. The best pH and ozone rate combinations were pH 8 and 0.8 g/h/L for scheme A, pH 8 and 1.6 g/h/L for scheme B and pH 7 and 0.8 g/h/L for scheme C. The ozonation post-treatment in these schemes, pH and ozone rates, the following COD and color reduction were achieved: 72% and 96% for scheme A; 94% and 85% for scheme B; 61% and 98% for scheme C. the COD and color levels attained were 851 mg/L and 906 Pt CU (from 22,660 Pt CU) in scheme A, 125 mg/L and 1900 Pt CU (from 12,670 Pt CU) in scheme B and 821 mg/L and 538 Pt CU (from 26,890 Pt CU) in scheme C. The model predicts that for scheme C at pH 7 and 4 g O₃/h, ca. 0.5 hour further ozonation treatment is needed to achieve 50 Pt CU color level and a polishing treatment or pH adjustment during ozonation is needed to achieve 100 mg/L COD. The results of this study using about 60 L total system volume showed that a combination of anaerobic and aerobic biological process in combination with ozonation as a pre-treatment and post-treatment is a promising option for larger scale treatment system for distillery wastewater.